Synthesis, spectroscopic, biological activities and DFT calculations of nickel(II) mixed-ligand complexes of tridentate Schiff bases - Demehin, Abidemi Iyewumi; Oladipo, Mary Adelaide; Semire, Banjo (Eclética Química, 2020)
Ni(II) mixed-ligand complexes of [NiLNH3] (where L= N-salicylidene-o-aminophenol (L1), N-(5-methoxysalicylidene-o-aminophenol) (L2) and N-(2-hydroxy-1-naphthalidene)-o-aminophenol) (L3) containing ONO tridentate Schiff bases and ammonia were synthesized and characterized by elemental analysis, infrared, ultraviolet-visible, proton and carbon-13 spectroscopies. Theoretical calculations were also performed on the optimized structures of the Ni(II) mixed-ligand complexes. The Infrared and ultraviolet-visible spectra of the complexes were calculated, and the results compared with the corresponding experimental spectra to augment the experimental structural identification. The elemental analysis data confirmed the formation of 1:1:1 [metal: Schiff base: ammonia] molar ratio. The NMR spectra showed that the Schiff bases coordinated to the Ni(II) ion via the two deprotonated phenolic oxygen and azomethine nitrogen atoms. The biological studies showed that the complexes exhibited higher antibacterial and antioxidant activities than the free Schiff base ligands.